Influence Business Environment and Strategic Leadership To Competitive Strategy and Business Performance (Studies in non-star hotels in Riau Islands Province) - YUDI HERTAWAN (Jurnal Bisnis Manajemen, 2015)
The tourism industry is one of the biggest foreign exchange earner of the country. Every year an increasing number of foreign tourists visiting Indonesia. Riau Islands Province ranked third nationally for number of foreign tourists after Bali and Jakarta, the number of tourists in 2012 amounted to 1.77 million people. Hotel services which is supporting the tourism industry is a sector that needs serious attention from the government and private sectors. Growth in the number of hotels in Riau Islands is very significant especially non-star hotel. In 2012, the number of non-star hotels in Riau Islands 309 from the previous number as many as 269 non-star hotel. This leads to the hotel were very tight competition. Besides, the hotel occupancy rate and average length of stay of non-star hotels tend to decline from 2010 to 2012. This study aims to produce a study on the influence of the business environment and strategic leadership to the competitive strategy and business performance. This type of research is descriptive and verification, the unit of analysis is a non-star hotels in Riau Islands. A sample size of 50 with the unit of observation is the manager or owner of the hotel. Analysis and hypothesis testing using the Partial Least Square (PLS). The test results indicate that the business environment and strategic leadership gives a greater influence on the performance of the business through a competitive strategy compared to the direct influence of the business environment and strategic leadership to business performance.Keywords: business environment, strategic leadership, competitive strategy, business performance.